COMPARATIVE SEASONAL ACTIVITY STUDY OF Dysaphis pyri (Boy.) AND Dysaphis reamuri (Mord.) ON SOME POME FRUITS VARIETIES - Nazar M. Al-Mallah (Mesopotamia Journal of Agriculture)
The results of studying the comparative seasonal activity of Dysaphis pyri (Boy.) and Dysaphis reamuri (Mord.) on some pome fruits varieties in Ninavah province during the year 2009 showed that the infestation by two species of aphids started during the last week of March, the infestation percentage by D. pyri reached its peak 37.78% of the east during the last week of April on Khatoni variety of pear, and reached 57.78% of the east during the first week of May on Ana apple variety. The average infestation percentage by Dysaphis reamuri (Mord.) reached 1st peak during the last week of April 35.56% of the east on Khatoni pear variety, and reached 53.33% of the east on Vestibilla apple variety during the first week of May. The result of Analytical study also show that a significant difference in infestation percentage and number of nymphs and adults of two species of aphids according to the kind of pome fruits varieties, direction and sampling date, and apple varieties were preferred by the two species of aphids in comparison with pear varieties, and D. pyri species was the most dominate species on pome fruits varieties.